ANALISIS PENGARUH KEPEMIMPINAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Study pada PT. Cahaya Agung Cemerlang - Semarang) - Purwanto, 14.05.51.0199; Muhaimin, Muhaimin (Students' Journal of Economic and Management, 2018)
This study aims to test and analyze the effect of Leadership, Motivation, and Compensation on Employee Performance. Analyzer used is Multiple Regression, as for to test hypothesis using t test. Data collection through questionnaires with measurements using Likert scale 5 (five) alternative answers. The research object is Employee PT. Cahaya Agung Cemerlang Semarang. The number of samples in this study is 100 respondents. Sampling technique using sample census. The result of the research shows that (1) Leadership has no effect on employee performance, (2) Motivation proved to have positive and significant effect on employee performance, (3) Compensation proved to have positive and significant effect on employee performance. Keywords: Leadership, Motivation, Compensation, Employee Performance